Alterações das características químicas do solo pela conversão de floresta nativa em sistemas de uso agrícola na região da Serra da Lua, Estado de Roraima - Golfetto, Deisy Camila (2010)
Land use changes such as conversion of natural ecosystems to agro ecosystems are shown to cause alterations in the the soil chemical characteristics. Over the last 40 years, land deforestation has occurred more intensively in the deforestation arc of Amazonian. The main objective of this research was to study soil chemical characteristics of red-yellow ultisol under differents land uses, in Roraima state, Northern Amazon, Brazil. The specific objectives were evaluate soil chemical characteristics of red-yellow ultisol under differents land uses havend native forest as reference and to measure the levels of soil organic matter (SOM) under differents land uses havend native forest as reference.The selected agro ecosystems of this study are located on the farm Umirizal the Bonfim city, Roraima States, (2º 33’36’’e 2º 43’ 12’’). Soil samplings were realized during december 2008, according to five treatments: native forest (FN), pasture fallow sistem (PP), pasture abandoned (DA); conventional tillage system (PC); Minimum tillage system (MT). An entirely random design with subdivided plots with five replicates, was used, and the systems allocated plots and subplots depths. Soil samples were collected in the following soil depths: 0-10; 10-20; 20-40 cm. Results showed that conversion of native forest for farming systems did not cause significant changes in the chemical properties of soils. The conversion of native forest for farming systems did not cause significant changes in soil chemical properties, despite the input of chemical fertilizers and soil disturbance. Most of the chemical remained below the critical level (lower class), except for exchangeable Ca in the DA system now for the class of medium fertility. The exchangeable bases and therefore the sum of bases found to be more prominent in the layer 0-10 cm. The active acidity was lower in DA and PP systems in relation to the Native Forest and potential acidity was lower in Native Forest, with a decrease in depth, also for other systems studied. The mineralization of organic matter and ash derived from burning the remains of the native vegetation provided improvements in chemical properties of the DA system surpassing the Native Forest. All systems were the major input of organic matter and consequently higher amount of total and effective CEC in the surface layer. The larger input of available phosphorus was in conventional tillage and the highest accumulation at the surface for all systems decreasing in depth. The soils, regardless of the system, gave values of phosphorus, mostly high, especially in the horizon surface, which results in low capacity to absorb phosphate.